PERANAN PEMBELAJARAN KONSEP DEMOKRASI PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN UNTUK MENINGKATKAN SIKAP DEMOKRATIS SISWA - Elly Hasan Sadeli; Ratna Kartika Wati (Sainteks, 2013)
Civic education aims to build the understanding of citizen in doing their right and compulsory as the member of people in every single past of life. Beside that, the civic education also try to develop the though of citizen, that is the citizen who are able to show their maturity of attitude, act, activity, speech and thought. In this research, the writers apply descriptive method combined with qualitative approach. The technique of data collecting used in this research are by doing interview, observation, documentation study and literary study. According to the research result, the writers have gained some conclusions, they are : 1) During the study of civic education, teachers are often giving some chances to students show their argumentation about the problems or issue of citizenship; The issues of citizenship meant above possibly come from the students’ social environment or the environment in general. The aim of giving chance to students in showing their arguments is to develop the athmosphere of democracy; 2) the obstacles during the learning process of democracy concept are the limited knowledge and information of democratic attitude in giving/showing argumentation that students have; 3) By giving learning process about democracy concept, the students are treated to be accustomed with the democratic attitude in responding every problem raises in the school, citizen or even citizenship issues in the scope of national. Keywords : Civic Education and Democracy